Territorial Dimension of Innovative Diffusion in the Socio-Economic Systems: Market Aspect - Zablodska, I.; Rohozian, Yu.; Khandii, O. (Економічний вісник Донбасу, 2022)
This work devotes to the territorial aspects of innovative diffusion in the socio-economic systems through the market provisions, since its development is becoming increasingly important to ensure the territories` competitiveness. The components of this article reveal the relationship between innovation diffusion and territorial marketing in the context of the development of socio-economic systems to ensure the well-being of communities, cities, regions and countries. It has been proven that modern changes in the economic environment force each territory to take certain marketing measures in order to win the best positions in the economic, social and environmental spheres, including by spreading innovations and using its own uniqueness. Thanks to the implementation of a pool of marketing activities, each community will be able to form a positive and recognizable image, the implementation of which will contribute to increasing competitiveness and attracting internal and external investment flows to ensure the sustainable development of the territory. This made it possible to draw a conclusion about the role of innovative diffusion marketing in the context of the development of socio-economic systems, which consists in the positioning of territories through the formation of their positive image, brand development, strengthening of reputation and accumulation of reputational capital. The authors investigate the marketing role of innovative diffusion in the context of the development of socio-economic systems based on the classification of forms, methods and types of this process, as well as by identifying the main groups of diffusers and their respective characteristics through the prism of the territorial aspect. Based on the results of the analysis of the pool of scientific works of foreign and Ukrainian scientists, a conclusion was made about the importance of studying the diffusion of innovations in socio-economic systems, taking into account the concept of sustainable development. It is noted that in practice, only representatives of the expert and scientific environment can assess the marketing role of innovation diffusion in the context of the development of territories (socio-economic systems) for their positioning. This allows to consider the process of positioning innovative diffusions within the framework of local socio-economic systems and investigate a sequence of actions to intensify this process. In order to research the methodological aspects of determination the marketing parameters of innovative diffusions of the local socio-economic systems, the authors identify the main parameters of positioning territorial communities through the prism of their sustainable development components. The procedure for positioning local socio-economic systems proposed, taking into account the provisions of the Concept of sustainable development and determination the marketing parameters of innovative diffusions.